2016
DOI: 10.1186/s12879-016-1923-2
|View full text |Cite
|
Sign up to set email alerts
|

Clinical presentations, diagnosis, mortality and prognostic markers of tuberculous meningitis in Vietnamese children: a prospective descriptive study

Abstract: BackgroundTuberculous meningitis in adults is well characterized in Vietnam, but there are no data on the disease in children. We present a prospective descriptive study of Vietnamese children with TBM to define the presentation, course and characteristics associated with poor outcome.MethodsA prospective descriptive study of 100 consecutively admitted children with TBM at Pham Ngoc Thach Hospital, Ho Chi Minh City. Cox and logistic regression were used to identify factors associated with risk of death and a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
39
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 41 publications
8
39
2
2
Order By: Relevance
“…Fever (90.5%), headache (71.4%) and cough (45.2%) were the most common symptoms, while more severe symptoms like neck stiffness, vomiting, and disturbance of consciousness were present in 35/42 (83.3%), 22/42(52.4%), and 14/42 (33.3%), respectively. The occurrence of these symptoms was similar or higher to those observed in previous studies [13][14][15][16]. In addition, children with TBM during hospitalization showed varying degrees of anti-tuberculosis druginduced hyperuricemia (23.8%) and hepatotoxicity (14.3%).…”
Section: Discussionsupporting
confidence: 86%
“…Fever (90.5%), headache (71.4%) and cough (45.2%) were the most common symptoms, while more severe symptoms like neck stiffness, vomiting, and disturbance of consciousness were present in 35/42 (83.3%), 22/42(52.4%), and 14/42 (33.3%), respectively. The occurrence of these symptoms was similar or higher to those observed in previous studies [13][14][15][16]. In addition, children with TBM during hospitalization showed varying degrees of anti-tuberculosis druginduced hyperuricemia (23.8%) and hepatotoxicity (14.3%).…”
Section: Discussionsupporting
confidence: 86%
“…GeneXpert) or culture was possible during the study period. It is possible that cases of TBM were missed, although Vietnamese children with probable or definite TBM had longer duration of symptoms before hospital review (median 19.5 days) than were seen in the current study [ 37 ]. Testing for Rickettsia spp.…”
Section: Discussionmentioning
confidence: 99%
“…In a pivotal study where adjunctive dexamethasone was found to decrease short term mortality in HIV‐1 uninfected patients with TBM, low glucose at presentation predicted poor outcome . In more recent studies, including those in children, CSF glucose, lactate, and protein levels have been linked to poor outcome . If these metabolic markers are simply markers of disease activity as in most forms of neurologic infection, then this finding is unsurprising.…”
Section: Pathogenic and Pathophysiologic Mechanisms Within The Brain mentioning
confidence: 99%